Individual carboxypeptidase D domains have both redundant and unique functions in Drosophila development and behavior. - Sidyelyeva, G.; Wegener, C.; Schoenfeld, B.P.; Bell, A.J.; Baker, N.E.; McBride, S.M.; Fricker, L.D. (Cellular and molecular life sciences. CMLS, 2010)
Metallocarboxypeptidase D (CPD) functions in protein and peptide processing. The Drosophila CPD svr gene undergoes alternative splicing, producing forms containing 1-3 active or inactive CP domains. To investigate the function of the various CP domains, we created transgenic flies expressing specific forms of CPD in the embryonic-lethal svr (PG33) mutant. All constructs containing an active CP domain rescued the lethality with varying degrees, and full viability required inactive CP domain-3. Transgenic flies overexpressing active CP domain-1 or -2 were similar to each other and to the viable svr mutants, with pointed wing shape, enhanced ethanol sensitivity, and decreased cold sensitivity. The transgenes fully compensated for a long-term memory deficit observed in the viable svr mutants. Overexpression of CP domain-1 or -2 reduced the levels of Lys/Arg-extended adipokinetic hormone intermediates. These findings suggest that CPD domains-1 and -2 have largely redundant functions in the processing of growth factors, hormones, and neuropeptides.